Eminent outlaws the gay writers who changed America - Bram, Christopher (New York Twelve, 2012)
Describes how the trailblazing, post-war gay literary figures, including Tennessee Williams, Gore Vidal, Truman Capote, and Allen Ginsberg, paved the way for newer generations, including Armistead Maupin, Edmund White, and Edward Albee.
Pt. 1. Into the fifties. Innocence ; The kindness of strangers ; Howl ; Soul kiss ; Going Hollywood -- pt. 2. The sixties. The great homosexual theater scare ; The medium is the messsage ; Love and sex and A single man ; The whole world is watching ; Riots -- pt. 3. The seventies. Old and young ; Love song ; Annus mirabilis ; White noise -- pt. 4. The eighties. Illness and metaphor ; Dead poets society ; Tale of two or three cities ; Laughter in the dark -- pt. 5. The nineties and after. Angels ; Rising tide ; High tide -- Rewriting America.
Includes bibliographical references (p. 351-354) and index.
UCWS-2696g donated by Prof. Eric Julian Manalastas - January 2016
Keywords: Gays' writings, American -- History and criticism; Authors, American -- 20th century; Gay authors -- United States